Sport et bicatégorisation par sexe : test de féminité et ambiguïtés du discours médical - Bohuon, Anaïs (Nouvelles Questions Féministes, 2008)
Dès les années 30, des sportives font l’objet d’un procès de virilisation dans des épreuves d’athlétisme en raison de morphologies jugées trop « masculines ». Ces athlètes se rapprochent des hommes non seulement par le physique, mais aussi par leurs performances. Des soupçons sont alors émis quant au sexe des sportives. En 1966, un test de féminité est instauré par le monde médical sportif afin de contrôler le sexe des concurrentes et s’assurer que celles-ci ne bénéficient pas d’avantages physiques que les femmes ne sont pas censées posséder. Notre article consiste à montrer les ambiguïtés des discours médicaux face aux controverses soulevées par le test de féminité qui, dévoilant les niveaux pluridimensionnels de l’identité sexuée, obligent le milieu médico-sportif à s’interroger sur la définition d’une « vraie femme ».
Number: 1
Keywords: 1900-1999; 1930-1939; 1960-1969; approches et analyses; cours; discipline; discours dominant; europe; france; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sport; systèmes d'oppressions; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques